EYE AND FOOT COORDINATION CONTRIBUTION ON PASSING SKILLS IN FUTSAL ATLET AT SDIT IQRA BENGKULU - Desrio Windoro (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Futsal is one of the most popular extracurricular by students at SDIT IQRA1 of Bengkulu City. This study aims to determine the contribution of eyes and feet coordination towards basic passing skills on futsal athletes at SDIT IQRA 1 of Bengkulu City. The method used in this study is quantitative correlation method. Population in this study is all students of sport futsal extracurricular while the sample is 20 students. The instruments in this study are test of Soccer Wall Volley Test from Barry L. Johnson and to  measure the passing skill by using passing practice test. Prerequisite data analysis used is normality test with Lilliefors, homogeneity test and contribution test. The data analysis used is Product Moment Correlation analysis with 5% significance level. Based on the results of the study, it is found that (1) there is a significant relationship between coordination of eyes and feet (X) to the accuracy of the passing indicated by r count = 0.90977 > r (0.05) (20) = 0.444. (2) There is a strong positive contribution of 82.768% between eyes and feet coordination (X) towards passing skill (Y) on futsal athletes at SDIT IQRA 1 of Bengkulu City.